1978
DOI: 10.1111/j.1469-8137.1978.tb01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Interpreting the Relationship Between the Amounts of Lead and Zinc in Plants and Soil on Metalliferous Wastes

Abstract: SUMMARY The lead and zinc contents of shoot material of Agrostis tennis, Festuca ovina and Minuartia verna and of the soil in which they were growing at an abandoned lead‐mining area on Grassington Moor, Yorkshire, England were determined. The relationship between the zinc contents of shoot material and soil was broadly linear. There was little increase, however, in the lead content of the shoot material over the range 500‐20000 μg g−1 lead in the soil. Above this value the lead content of the shoot material i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 32 publications
2
3
0
1
Order By: Relevance
“…With lead, there is only a poor relationship between soil-lead levels and plant levels. This is emphasized by the fact that plants growing on sites with similar degrees of lead contamination display widely varying concentrations of lead in their aerial organs and is in agreement with the findings of Barry and Clark (1978). Aerial contamination can be ruled out as a possible explanation because all leaves were thoroughly washed prior to processing.…”
Section: Discussionsupporting
confidence: 74%
“…With lead, there is only a poor relationship between soil-lead levels and plant levels. This is emphasized by the fact that plants growing on sites with similar degrees of lead contamination display widely varying concentrations of lead in their aerial organs and is in agreement with the findings of Barry and Clark (1978). Aerial contamination can be ruled out as a possible explanation because all leaves were thoroughly washed prior to processing.…”
Section: Discussionsupporting
confidence: 74%
“…Regarding the exchangeable cations (Table 3b), only Pb and Zn had higher than normal levels. These values for exchangeable cations were also similar to those recorded elsewhere (Ernst 1968b;Davies 1971;Simon 1978;Barry & Clark 1978). The principal The principal component analysis of the floristic data (Fig.…”
Section: Principal Component Analysissupporting
confidence: 61%
“…Similar uptake patterns have been proposed by Berry (1986) from laboratory and field studies. Barry and Clark (1978) have also reported that the range of substrate metal concentrations over which measurements are made, dictates the plant/substrate relationship. Thus a plant may exhibit all of the above uptake patterns over different concentration ranges of the element in the substrate.…”
Section: Introductionmentioning
confidence: 99%